Study of Kinetics and Adsorption Isotherm of Methylene Blue Dye using Tannin Gel from Ceriops tagal - Thamrin Azis; La Ode Ahmad; Keke Awaliyah; Laode Abdul Kadir (Jurnal Kimia Sains dan Aplikasi, 2020)
Research on the equilibrium and adsorption kinetics of methylene blue dye using tannin gel from the Tingi tree (Ceriops tagal) has been carried out. This study aims to determine the capacity and adsorption kinetics of tannin gel against methylene blue dye. Several parameters, such as the effect of contact time, pH, and methylene blue dye concentration on adsorption, were also studied. Based on the research results, the optimum adsorption process is a contact time of 30 minutes and a pH of 7. The adsorption capacity increased to a concentration of 80 mg/L with a maximum adsorption capacity (qm) of 49.261 mg/g. The adsorption process follows the pseudo-second-order adsorption kinetics model and the Langmuir isotherm model.